2021
DOI: 10.1590/2175-6236104309
|View full text |Cite
|
Sign up to set email alerts
|

Um Arquivo sobre Teatro e Educação: problematizações no campo da invenção

Abstract: Resumo: Inspirada no trato arquivístico legado pelo pensador francês Michel Foucault, esta reflexão debruçou-se sobre a tarefa de estabelecer um inventário da produtividade discursiva relativa ao campo das práticas que aliam teatro e educação, tomando por base empírica artigos concernentes ao tema e publicados em 58 periódicos da área educacional. Objetivou-se flagrar descontinuidades, regularidades e aleatoriedades em tal campo discursivo, culminando em mirar pela perspectiva crítica o que no presente emana c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…So, the use of visual art-based techniques has been increasingly tested to help students connect with their emotions. Other creative art techniques, such as fiction (Gartner et al, 1992; Cohen, 1998; Hjorth, 2005), science fiction (Keane, 1999; Smith et al, 2001) or theatre (Gomes, 2021) have also shown many advantages.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…So, the use of visual art-based techniques has been increasingly tested to help students connect with their emotions. Other creative art techniques, such as fiction (Gartner et al, 1992; Cohen, 1998; Hjorth, 2005), science fiction (Keane, 1999; Smith et al, 2001) or theatre (Gomes, 2021) have also shown many advantages.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among creative arts techniques, literary forms such as fiction (Gartner, Bird et Starr, 1992; Cohen, 1998; Hjorth, 2005), science fiction (Keane, 1999; Smith et al, 2001) or drama (Gomes, 2021) have shown many advantages. Fiction allows us to go beyond the routines of the present (Nordqvist et Gartner, 2020).…”
Section: Introductionmentioning
confidence: 99%